2001
DOI: 10.1128/aac.45.1.187-195.2001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacies of Lipophilic Inhibitors of Dihydrofolate Reductase against Parasitic Protozoa

Abstract: Competitive inhibitors of dihydrofolate reductase (DHFR) are used in chemotherapy or prophylaxis of many microbial pathogens, including the eukaryotic parasites Plasmodium falciparum and Toxoplasma gondii. Unfortunately, point mutations in the DHFR gene can confer resistance to inhibitors specific to these pathogens. We have developed a rapid system for testing inhibitors of DHFRs from a variety of parasites. We replaced the DHFR gene from the budding yeast Saccharomyces cerevisiae with the DHFR-coding region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…A number of the compounds in our library, along with others from the archives of the National Cancer Institute and the Walter Reed Army Institute of Research, were recently found to be active in a yeast complementation assay using Saccharomyces cerevisiae in which the native yeast gene was replaced with either the entire difunctional DHFR-TS gene or the discrete DHFR domain of C. parvum (7,40). In the present paper, we report data on 93 compounds from the archival collection of the DanaFarber Cancer Institute (DFCI) as in vitro inhibitors of recombinant C. parvum and human DHFR activity in a spectrophotometric assay.…”
mentioning
confidence: 99%
“…A number of the compounds in our library, along with others from the archives of the National Cancer Institute and the Walter Reed Army Institute of Research, were recently found to be active in a yeast complementation assay using Saccharomyces cerevisiae in which the native yeast gene was replaced with either the entire difunctional DHFR-TS gene or the discrete DHFR domain of C. parvum (7,40). In the present paper, we report data on 93 compounds from the archival collection of the DanaFarber Cancer Institute (DFCI) as in vitro inhibitors of recombinant C. parvum and human DHFR activity in a spectrophotometric assay.…”
mentioning
confidence: 99%
“…However, drug screening in M. smegmatis has not always been an accurate predictor of activity (28,29) or the mechanism of action (1,22) in M. tuberculosis. In addition, S. cerevisiae has several advantages that we have exploited to develop similar systems for the screening of inhibitors of the DHFR enzymes from P. falciparum, C. parvum, and P. carinii DHFRs (2,19,36,43). First, plasmids that carry a centromere are maintained at one copy per cell in yeasts (37), so the level of expression of an introduced gene can be controlled even on a plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…The first step was to determine the relative potencies of these compounds compared with that of WR99210 by a simple radial assay with the TB-yeast (19). Briefly, TB-yeast was streaked from the center to the edge of a plate to make a template.…”
Section: ϫ10mentioning
confidence: 99%
See 1 more Smart Citation
“…The yeast was grown in 96-well plates at the indicated concentrations of the drugs dissolved in DMSO. To increase the sensitivity of the yeast to DHFR inhibitors, both the control and the drug-containing wells contained 1 mM sulfanilamide (13). The growth of the yeast in each well was assessed by reading the optical density at 650 nM after approximately 24 h of incubation at 30°C, and the growth in any well was compared with the growth of that strain in solvent alone.…”
Section: Vol 49 2005 De Novo Synthesis Of Novel Antifolate Antimalamentioning
confidence: 99%